Ambient Air Quality Detection System Powered by Internet of Things-Based Sansevieria Plant (Case Study of Manduro Health Center) - Sinta Winda Purnamasari; Farida Arinie Soelistianto; Mochammad Junus; Rachmad Saptono (West Science Interdisciplinary Studies, 2024)
Puskesmas Manduro is one of the public health service centers located at Jl. Raya Ngoro KM 14, Manduro MG Village, Ngoro District, Mojokerto Regency, East Java. As a basic health service center, it is important to monitor air quality and maintain air quality in accordance with the Environmental Quality Standard (SBMKL). This study aims to design an Internet of Things-based air quality detection system that utilizes Sansevieria plants as one of the natural solutions in absorbing air pollution levels. The method used is the research and development method which includes system design, tool making, website design, tool integration, and system testing. The sensors used are MQ-7 sensors for carbon monoxide gas, MQ-135 sensors for nitrogen dioxide gas, MQ-131 sensors for ozone gas, Dust GP2Y1010AU0F sensors for PM2.5, and DHT22 sensors for temperature and humidity. The results of testing the system for three days obtained the average temperature 30.64C, humidity 73.62%, CO 735.63 µg/m³. NO2 27.30 µg/m³, O3 32.13 30 µg/m³, and PM2.5 2.14 µg/m³. Based on the test results that have been carried out, it shows that the air quality monitoring system can provide data, graphs, and indicator levels for the Air Pollution Standard Index (ISPU). Air quality data obtained from sensors can be displayed on the LCD and also displayed in real-time through the website.